Comparação entre rotas de processamento para a produção de fitas de espessura micrométricas de ligas de titânio - Reis, Carolina (Universidade Federal de São Carlos, 2025)
The industrial use of titanium and its alloys began approximately 75 years ago, initially driven by military and aeronautical applications. Today, these materials are widely employed in aerospace, medical, and sports sectors, owing to the ability to tailor mechanical properties through microstructural control, influenced by chemical composition and processing routes. For the production of pure titanium and titanium alloy foils with micrometer-scale thickness, three processes are commonly applied: rolling, rapid solidification via melt overflow, and tape casting. This work evaluated the main aspects of each route without identifying a clearly advantageous process. A literature review revealed overlapping geometric ranges among the methods, with thicknesses between 230 and 740 μm and the potential for producing foils with widths of several tens of centimeters and lengths on the order of meters. All routes were found capable of generating dense microstructures with grain sizes in the range of tens of micrometers. However, the lack of detailed analyses of microstructure and properties limited conclusions regarding the interchangeability of one process over another for producing micrometer-thick titanium foils. Despite the specific features of each processing route, all of them are applied to a common sector: aerospace. In this field, α, α+β, and Al-rich alloys predominate. Nevertheless, the β alloy Ti-15Mo-3Al-3Nb (wt.%) was identified as a promising alternative to the traditionally used Ti-6Al-4V (wt.%), as it exhibits comparable or superior mechanical properties. It was also observed that the choice of the most suitable process depends on economic factors such as labor, equipment, raw material costs, and production volume. However, establishing this relationship would require an economic batch size analysis, which lies beyond the scope of this work.
Comparison of processing routes for the production of micrometer-thick titanium alloy ribbons
Keywords: Fitas; Espessura micrométrica; Ligas de titânio; Laminação; Solidificação rápida; Tape casting; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA